EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE 5 FASE TERHADAP HASIL BELAJAR FISIKA SISWA - Anwar Salam; Nengah Maharta; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
Learning conventional always centered around teacher, impressed harm to the students especially of students which is more capable low visible tend more passive in learning, so necessary kind of classroom that can make students incentivized and the results of learning increase, that is learning cycle 5 phase.The study is done to know the effectivity of model learning lc5e consisting of 5 phase against the study result of the students. The purpose of this research was to determine the efficiency of LC5E learning model consisting of 5 phases of acquisition of student learning outcomes: ( 1 ) the difference average study result of the students who learning use the model of learning lc5e with conventional ( in ) ( 2 ) a model of learning more effective in increasing study result of the students in learning physics. The design of this research was using design one shot case study. Study result of the measured from value the evaluation posttest. From the test already done show that: ( 1 ) There have difference average study result of the class between lc5e and a class conventional ( in ) ( 2 ) learning lc5e effective in increasing study result of the students.Keyword : Learning result, Learning cycle 5 fase